1987
DOI: 10.1111/j.1476-5381.1987.tb11384.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of platelet activating factor in endotoxin‐induced pulmonary platelet recruitment in the guinea‐pig

Abstract: 1 Exposure of conscious guinea-pigs to an aerosol of endotoxin (25-100ug ml-') resulted in a doserelated, progressive accumulation of platelets in the thoracic region. Accumulation of" 'indium oxine labelled erythrocytes was not observed following exposure to an aerosol of endotoxin (50 fig ml-'). 2 Pretreatment of guinea-pigs with the selective platelet activating factor (Paf)-antagonists. CV-3988 or brotizolam resulted in a dose-related inhibition of endotoxin-induced pulmonary platelet recruitment. Pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 27 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…When conscious guinea pigs were exposed to an aerosol of endotoxin (25-100 pg ml-l), pretreatment with the hetrazepinoic PAF antagonist brotizolam (0.5-1 mgikg i.v.) inhibited the endotoxin-induced pulmonary platelet recruitment in a dose-related manner [133,134]. Thoracic accumulation of "lIndium-labeled platelets was followed for 150 min, being maximal at this time point.…”
mentioning
confidence: 99%
“…When conscious guinea pigs were exposed to an aerosol of endotoxin (25-100 pg ml-l), pretreatment with the hetrazepinoic PAF antagonist brotizolam (0.5-1 mgikg i.v.) inhibited the endotoxin-induced pulmonary platelet recruitment in a dose-related manner [133,134]. Thoracic accumulation of "lIndium-labeled platelets was followed for 150 min, being maximal at this time point.…”
mentioning
confidence: 99%
“…PAF itself or combining with LPS can promote platelet activation and recruitment and worsen endotoxin-induced lung injury [29], [30]. Our study has showed that plasma PAF levels were significantly elevated in LPS-challenged F508del mice compared the wildtype mice.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study showed that PAF can stimulate mononuclear cells of peripheral blood leading to the release of TNF-α and IL-6 in viral infection [36]. PAF itself or combined with LPS can promote platelet activation and recruitment and worsen endotoxin-induced injury [37,38]. Therefore, PAF and cytokines potentiate each other's effects in vivo to modulate the immune response [39].…”
Section: Discussionmentioning
confidence: 99%